A rare case of an isolated triquetrum body fracture in a 14-year-old boy - Nikolaus Horras; Winfried Barthlen; Peer Wildbrett (Wolters Kluwer Medknow Publications, 2012)
Isolated carpal fractures are uncommon injuries usually caused by a fall on the outstretched hand. The patient might present with non-specific clinical signs and X-ray diagnosis might be difficult due to bone overlay. An isolated triquetrum body fracture is an absolute rarity. The treatment is easy and the outcome excellent but if missed, degenerative changes with chronic pain and impaired movement might be the consequence.